(untitled) (Research, Society and Development, 2020)
The main objective of this work was to survey areas contaminated by organic compounds in the watershed of the Rio das Velhas, in Minas Gerais. Data from the State Foundation for the Environment - FEAM, through the Minas Gerais Inventory of Contaminated and Remedied Areas for 2019, was used. The results showed that the contaminated and remedied areas are concentrated in the metropolitan region of Belo Horizonte, being fuel resellers and related stations the main activity responsible for the contamination, and it occurs most of the time by leakage or infiltration. The compounds present in the fuels are toxic and have the potential to cause damage to the health of the population and the environment. The results also showed that 54.24% of the declared areas are already rehabilitated for declared use. The study concluded that although the Inventory of Contaminated and Remediated Areas contains important information to subsidize the management of contaminated areas, the number of declared areas is still low in relation to the expressive number of activities with potential for contamination.